Tinjauan Kenyamanan Fasilitas Taman ( Studi Kasus : Taman Lansia PIK ) - Nugroho, Rakie Catur; Amelia, Siska (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2022)
Taman Lansia PIK is an RW park located in the Penggilingan, East Jakarta. Overall, the facilities provided at Taman Lansia PIK have met the requirements regarding the provision and utilization of green open space. This research aims to find out the comfort of the park facilities in Taman Lansia PIK. The method used is qualitative with descriptive analysis. Data collection in the form of surveys and observations directly to Taman Lansia PIK then communicated with the theoretical studies that have been obtained. So that conclusions were obtained about the condition of the Taman Lansia PIK. The results of the research showed that the facilities of the park are in accordance with the provisions, only the design of the facilities - the park facilities do not take into account the technical facilities and accessibility of the environment. This can reduce comfort for park visitors, especially the elderly and people with disabilities. The maintenance of the park was not maximized and caused the beauty of the park to be reduced and the park facilities suffered a lot of damage. Therefore, it is recommended to the manager of Taman Lansia PIK, in order to renovate and maximize the maintenance of the park.